Resultados clínicos antes e após a implantação do protocolo acerto no Hospital de Câncer de Mato Grosso - Costa, Haracelli Christina Barbosa Alves Leite da (2013)
The ACERTO protocol (ACEleração da Recuperação TOtal PósOperatória) is a program aimed at enhancing postoperative recovery of patients. The implementation of this protocol improved the results in one university hospital reducing the length of stay in 2 days. AIM: We compared the postoperative clinical outcome of patients submitted to oncological surgeries at Hospital de Câncer de Mato Grosso before and after the implementation of the Acerto protocol. METHODS: 271 patients were prospectively followed up in two periods: firstly, from April to May 2010 (n=101) including those submitted to conventional perioperative prescriptions (Phase 1) and secondly, from September to October 2010 (n=171) including those who received the Acerto protocol (Phase 2). The main outcome variables were: preoperative fasting time, day of postoperative refeeding, hydration volume, and length of postoperative stay. RESULTS: Comparing the two phases there was a decrease of approximately 50% of the preoperative fasting time (14,7 [4-48] h vs 7,2 [1-48] h, p<0,001), a fall of nearly 35% of the volume of the immediate postoperative intravenous fluids (p<0.001), 47% in the 1st PO day (p<0.001), 28% in the 2nd PO day (p=0.04), and a global reduction of 23% (p<0.001). Most patients was replenished until 24 hours after the surgical procedure with no difference (p = 0.44) between the phase 1 (95/101 cases, 94%) and phase 2 (162/169 cases, 95.8%). There was no difference in the length of postoperative stay between the two phases (3,9 [0-51] vs. 3,2 [0-15] days; p=0.52). However, in the subset of patients submitted to the operations bearing a preoperative fast up to 5h we found a reduction of one day of hospitalization (3.8 [0-51] vs 2.5 [0-15] dias, p=0,03). CONCLUSIONS: The adoption of the routines of the Acerto protocol is safe and feasible in oncologic subjects. After the implementation of the Acerto protocol there was a decrease of intravenous fluids volume and when preoperative fast time was shorter than 5h the length of stay was reduced.